TI_GERICHTE 52.2025.275 vom 28. Juli 2025 , Commesse pubbliche. Valutazione delle referenze. Interpretazione delle regola di gara. - TI Tribunale d'appello (2025)
Commesse pubbliche. Valutazione delle referenze. Interpretazione delle regola di gara.